Mobile Legends Gameplay and Student Outcomes in Islamic Religious Education: Permainan Mobile Legends dan Dampak terhadap Hasil Belajar Siswa dalam Pendidikan Agama Islam - Siregar, Alde Rizky Pratama; Miswar, Miswar (Indonesian Journal of Innovation Studies, 2026)
General Background: Digital gaming has become an integral part of adolescent life, influencing various dimensions of their learning experiences. Specific Background: Mobile Legends, a popular multiplayer online battle arena game, is widely played by students, yet its relationship with Islamic Religious Education (PAI) learning outcomes remains underexamined. Knowledge Gap: Previous studies predominantly address general academic performance, leaving a gap regarding how gaming behavior interacts specifically with PAI learning. Aims: This study examines the influence of Mobile Legends playing intensity on PAI learning outcomes among students at Sinar Husni Private High School. Results: Using a quantitative survey of 67 students and simple linear regression analysis, findings show a very weak positive but statistically insignificant correlation (R = 0.171; R² = 0.029; p = 0.166), indicating that gaming activity does not directly predict PAI academic performance. Novelty: Unlike earlier research emphasizing negative academic effects, this study highlights the potential indirect benefits of gaming—such as teamwork, decision-making, and emotional regulation—within the context of religious education. Implications: The findings suggest that regulated gaming need not be viewed strictly as detrimental; instead, educators may leverage its constructive elements to support character development and design more engaging PAI learning strategies. Highlights: Mobile Legends shows a very weak and non-significant influence on PAI learning outcomes. Gaming may offer indirect benefits such as teamwork, decision-making, and emotional regulation. PAI teachers can integrate positive gaming elements to support character-based learning. Keywords: Mobile Legends, Islamic Religious Education, Learning Outcomes, Digital Games, Student Behavior